Biophilic Architecture in the Livable City of Melbourne CBD - Thampanichwat, Chaniporn; Wongvorachan, Tarid; Somngam, Panyaphat; Petlai, Taksaporn; Sirisakdi, Limpasilp; Anuntavachakorn, Pakin; Bunyarittikit, Suphat; Prasarnklieo, Wacharapong (My University, 2025)
Amid continuous urban population growth and urbanization’s environmental and social challenges, livable cities have become a key priority for governments. Among the various factors influencing urban livability, architectural design integrating natural elements plays a critical role. Melbourne consistently ranks as one of the world’s most livable cities, with its Central Business District (CBD) serving as its core. Since a previous study has highlighted a research gap concerning the role of architecture in livable cities and indicated that the characteristics of biophilic architecture remain unclear, this study addresses the following question: What are the attributes of biophilic architecture in the CBD of the livable city of Melbourne? Subsequently, buildings exhibiting characteristics of Biophilic architecture were surveyed, and photographs capturing the most representative aspects of each building were documented. These characteristics were then coded and analyzed using statistics. The study found that Biophilic architecture is extremely rare in Melbourne’s CBD, with only four of 6375 properties (0.06%) identified as such. The most prominent attributes include connection to nature, natural color tones, and light modulation shaped by the city’s grid layout and strong sunlight. However, the dominance of concrete structures and heritage regulations constrains formal diversity. While Melbourne may not provide abundant examples, its context offers valuable insight into how urban form and policy shape biophilic expression. Future studies should extend this comparative approach to other cities to better understand context-specific adaptations of biophilic design.
Keywords: architecture; biophilic architecture; biophilic design; Central Business District; livable city; Melbourne